Experimental determination of the aerodynamic coefficients of spinning bodies. (May 2019) - Nguyen, S.; Corey, M.; Chan, W.; Greenhalgh, E.S.; Graham, J.M.R.
ABSTRACT: To accurately predict the probabilities of impact damage to aircraft from runway debris, it is important to understand and quantify the aerodynamic forces that contribute to runway debris lofting. These lift and drag forces were therefore measured in experiments with various bodies spun over a range of angular velocities and Reynolds numbers. For a smooth sphere, the Magnus effect was observed for ratios of spin speed to flow speed between 0.3 and 0.4, but a negative Magnus force was observed at high Reynolds numbers as a transitional boundary layer region was approached. Similar relationships between lift and spin rate were found for both cube- and cylinder-shaped test objects, particularly with a ratio of spin speed to flow speed above 0.3, which suggested comparable separation patterns between rapidly spinning cubes and cylinders. A tumbling smooth ellipsoid had aerodynamic characteristics similar to that of a smooth sphere at a high spin rate. Surface roughness in the form of attached sandpaper increased the average lift on the cylinder by 24%, and approximately doubled the lift acting on the ellipsoid in both rolling and tumbling configurations.